The effect of an unstructured, moderate to vigorous, before-school physical activity program in elementary school children on academics, behavior, and health - Tompkins Connie L; Hopkins Jacob; Goddard Lauren; Brock David W (BMC, 2012)
Abstract Background Physical inactivity has been deemed a significant, contributing factor to childhood overweight and obesity. In recent years, many school systems removed recess and/or physical education from their curriculum due to growing pressure to increase academic scores. With the vast majority of children's time spent in school, alternative strategies to re-introduce physical activity back into schools are necessary. A creative yet underutilized solution to engage children in physical activity may be in before-school programs. The objective of the proposed study is to examine the effect of an unstructured, moderate to vigorous, before-school physical activity program on academic performance, classroom behavior, emotions, and other health related measures. Methods/Design Children in 3rd-5th grade will participate in a before-school (7:30-8:15 a.m.), physical activity program for 12 weeks, 3 days a week. Children will be able to choose their preferred activity and asked to sustain physical activity of moderate to vigorous intensity with individual heart rate monitored during each session. Discussion The proposed study explores an innovative method of engaging and increasing physical activity in children. The results of this study will provide evidence to support the feasibility of an unstructured, moderate to vigorous, before-school physical activity program in children and provide insight regarding the ideal physical activity intensity and duration necessary to achieve a positive increase in academic performance. Trial registration ClinicalTrials.gov Identifier: NCT01505244